2009
DOI: 10.1007/s10508-009-9551-1
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Follow-Up Study of Swedish Adults with Gender Identity Disorder

Abstract: This follow-up study evaluated the outcome of sex reassignment as viewed by both clinicians and patients, with an additional focus on the outcome based on sex and subgroups. Of a total of 60 patients approved for sex reassignment, 42 (25 male-to-female [MF] and 17 female-to-male [FM]) transsexuals completed a follow-up assessment after 5 or more years in the process or 2 or more years after completed sex reassignment surgery. Twenty-six (62%) patients had an early onset and 16 (38%) patients had a late onset; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 13 publications
4
90
1
3
Order By: Relevance
“…Therefore, the main effect we found for transition status predicting lifetime SI must be interpreted in light of the significant interaction with discrimination experiences. In other words, this finding supports the notion that transitioning/gender affirmation, although associated with some reductions in gender dysphoria, 27 appears also to be associated with an increase in psychological distress-possibly because of the impact of gender identity-related discrimination experienceswhich aligns well with Meyer's minority stress model. Thus, the significant interaction term suggests that neither discrimination experiences nor transition status independently predicts SI; however, our ability to draw conclusions from this result is limited because of the cross-sectional nature of the design and continued difficulties in operationalizing transition status.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, the main effect we found for transition status predicting lifetime SI must be interpreted in light of the significant interaction with discrimination experiences. In other words, this finding supports the notion that transitioning/gender affirmation, although associated with some reductions in gender dysphoria, 27 appears also to be associated with an increase in psychological distress-possibly because of the impact of gender identity-related discrimination experienceswhich aligns well with Meyer's minority stress model. Thus, the significant interaction term suggests that neither discrimination experiences nor transition status independently predicts SI; however, our ability to draw conclusions from this result is limited because of the cross-sectional nature of the design and continued difficulties in operationalizing transition status.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore the findings reported relate to NSSI behaviour pre-assessment and before the commencement of treatment and possibly transition. As there is strong evidence of improved psychological and social functioning following social gender role transition (Cohen et al, 1997;Johansson et al, 2010;Murad et al, 2010) the high rates of NSSI behaviour in this study may be a reflection of the specific population selected. A study using similar methodology but selecting a population of trans people attending clinical services and at different stages of the transitional and treatment process found that trans participants had a significantly higher rate of NSSI compared to a control sample (Davey et al, 2015).…”
Section: Nssi and Trans Peoplementioning
confidence: 83%
“…Mdn ( Cinsiyet geçiş sürecinin uzun vadede ruhsal iyilik hali ve genel işlevselliğe olumlu etkilerinin olduğu izlem çalışmaların-da saptanmıştır (Johansson ve ark. 2010, Ruppin ve Pfafflin 2015.…”
Section: (Ss)unclassified